Sjögren syndrome from a dermatological perspective: A retrospective study of 185 SSA‐Ro positive patients - Fiona André; Martha Bujak; Nina Frischhut; Andreas Kronbichler; Norbert Sepp; Gudrun Ratzinger; Barbara Böckle (Wiley, 2024)
Abstract Background Sjögren syndrome (SS) is a systemic autoimmune disease characterised by oral and ocular mucosal dryness. Objectives Our study focused on skin manifestations of SS. The differences between primary SS (pSS) and secondary SS (sSS) were investigated. Furthermore, we elucidated factors predicting internal organ involvement. Methods This was a single centre retrospective cohort study. We analysed clinical and laboratory data from 185 Ro‐SSA positive SS patients between January 2000 and December 2016. Results Skin manifestations were present in 74.9% (n = 137) of SS patients. Dermatitis and Lupus erythematosus (LE)‐specific skin manifestations were present in 34.1% (n = 63) and 21.6% (n = 40) of SS patients respectively. 65.9% (n = 122) of SS patients had internal organ involvement, with 53% (n = 98) presenting neuropsychiatric manifestations. Several risk factors for internal organ involvement were identified: presence of myalgia/arthralgia (odds ratio [OR] = 3.05, confidence interval [CI] 1.29−7.22), fatigue (OR = 2.53, CI 1.11−5.73) and age older than 50 years (OR = 2.23, CI 1.01−4.93). Conclusions Internal organ involvement is frequent in SS, however there is no significant difference between pSS and sSS concerning its occurrence.